Market Size Effects in New New Trade Theory - Benjamin Jung; Gabriel Felbermayr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Increasing-returns-to-scale imperfect competition trade models predict a more than proportionate relationship between the larger country s share in world endowments and its share in producing firms: the so called home market effect (HME). We show that the single-sector Melitz (2003) model features a weak and a strong HME, even in the absence of a second sector. The HMEs are generally non-linear; they are magnified by lower trade costs or by more pronounced productivity dispersion. The model implies that market size differences translate into regional inequality. In contrast to the traditional formulation with a linear outside sector, trade liberalization leads to convergence of real per capita income. In terms of demand shares, a HME holds if demand shocks are due to endowment shocks but reverses in the case of productivity shocks.
Keywords: F12; F15; R12; 330